Parametric optimization and kinetic study of l‐lactic acid production by homologous batch fermentation of Lactobacillus pentosus cells. (13th August 2020) - Wang, Jianfei; Huang, Jiaqi; Jiang, Shaoming; Zhang, Jing; Zhang, Quanquan; Ning, Yuchen; Fang, Mudannan; Liu, Shijie
Abstract: Parametric optimization always plays important roles in bioengineering systems to obtain a high product yield under the proper conditions. The parametric conditions of lactic acid production by homologous batch fermentation of Lactobacillus pentosus cells was optimized by the Box–Behnken design. The highest l ‐lactic acid yield was obtained as 0.836 ± 0.003 g/g glucose with the productivity of 0.906 ± 0.003 g/(L × H) under the optimum conditions of 34.7 °C, pH 6.2, 148 rpm agitation speed, and 9.3 g/L nitrogen source concentration determined by quadratic response surface with high accuracy. The adequate kinetic models of cell growth rate, lactic production rate, and glucose consumption rate were also established to describe the fermentation behavior of L. pentosus cells with the correlation coefficients of 09985, 0.9990, and 0.9989, respectively. Abstract : Parametric optimization and kinetic study of l‐lactic acid production by homologous batch fermentation of Lactobacillus pentosus cells.